Возраст и скорость роста зеленых лягушек (Pelophylax esculentus complex) Нижнего Добрицкого пруда (Змиевской район Харьковской области) - Усова, E.E. (Вісник Харківського національного університету імені В. Н. Каразіна. Серія: біологія, 2014)
С помощью скелетохронологии изучено 104 представителя Pelophylax esculentus complex (18 P. ridibundus, 66 диплоидных P. esculentus и 20 триплоидных P. esculentus) из гемиклональной популяционной системы Нижнего Добрицкого пруда (N 49°33'22", E 36°18'39"; Змиевский район Харьковской области, пойма реки Гомольша), расположенной на территории Национального природного парка «Гомольшанские леса». По срезам 4-й фаланги длиннейшего пальца задней конечности установлен возраст изученных особей, рассчитаны их годовые приросты. Максимальная скорость роста и для самцов, и для самок наблюдается перед 4-й зимовкой, что соответствует достижению половой зрелости в возрасте 5 лет. Различия в скорости роста P. ridibundus, ди- и триплоидов P. esculentus статистически незначимы. Age and growth rate of green frogs (Pelophylax esculentus complex) of the Lower Dobritsky pond (Zmiyiv district, Kharkiv region) E.E.Usova With the use of skeletochronology 104 specimens from the population of Pelophylax esculentus complex (18 P. ridibundus, 66 diploid P. esculentus, and 20 triploid P. esculentus) inhabited the Lower Dobritsky pond (N 49°33'22 ", E 36°18'39"; Zmiyiv district of the Kharkiv region, the floodplain of the Gomolsha River at the National Natural Park "Gomilshanski lisy") were studied. The age of the individuals was estimated histologically by the sections of the longest toe’s 4th phalanx and determination of annual growth marks. The annual growth rates were calculated. The maximum growth rate was observed between the 4th and 5th hibernations for both males and females. It has been shown that differences in the growth rates between P. ridibundus, di- and triploid P. esculentus are statistically insignificant.
Keywords: Pelophylax esculentus complex; Скелетохронология